1992
DOI: 10.1346/ccmn.1992.0400301
|View full text |Cite
|
Sign up to set email alerts
|

39K Solid-State NMR Studies of Potassium Tecto- and Phyllosilicates: The In Situ Detection of Hydratable K+ in Smectites

Abstract: Abstract--We report the first application of 39K solid-state NMR to the study of tecto-and phyllosilicates. Under high field (11.7 Tesla) and with the application of a spin-echo sequence, informative 39K spectra can be obtained for several compounds of interest to the geologist and the agronomist. Tectosilicates and phyllosilicates can be distinguished from the uncorrected frequency (Sc6) of the observed NMR peak. A series of montmorillonites submitted to increasing numbers of wetting and drying cycles was stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
45
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(56 citation statements)
references
References 23 publications
11
45
0
Order By: Relevance
“…A previous 39 K study of a similar potassium feldspar (orthoclase) and several sheet silicates including muscovite used partially oriented single crystals at 11.7 T, and noted surprisingly broad peaks [31]. Peak positions obtained in that study cannot be directly compared with the new data at 18.8 T because powder averages were not obtained.…”
Section: "Low γ" Nuclides At 188 Tmentioning
confidence: 88%
“…A previous 39 K study of a similar potassium feldspar (orthoclase) and several sheet silicates including muscovite used partially oriented single crystals at 11.7 T, and noted surprisingly broad peaks [31]. Peak positions obtained in that study cannot be directly compared with the new data at 18.8 T because powder averages were not obtained.…”
Section: "Low γ" Nuclides At 188 Tmentioning
confidence: 88%
“…The 2 peaks observed for fully dehydrated samples were assigned to 2 different interlayer sites. Lambert et al (1992) report data obtained with a Kmontmorillonite submitted to wetting and drying (W-D) cycles. Figure 7 gives 39K solid-state NMR spectra of potassium in montmorillonite pastes prepared with samples submitted to 0, 11 and 100 W-D cycles and after a replacement of exchangeable K by Sr in the 100 W-D sample.…”
Section: Solid-state Nmr and Far-ir Spectroscopy Of Compensating Cationsmentioning
confidence: 99%
“…For example static 39 K NMR spectra from a range of model inorganic potassium salts showed relatively small dipolar coupling, resulting in sharp powder pattern features of the observed central transition allowing accurate extraction of the quadrupole parameters as chemical shift anisotropy appeared to make only a very small contribution [34]. In potassium-containing aluminosilicates it has been shown that from the position of the centre-of-gravity (cg) of the static 39 K resonances, the tectosilicate orthoclase (~205 ppm) could be distinguished from phyllosilicates in which the cg position is below 40 ppm [35]. Potassium NMR could also distinguish structural and exchangeable potassium in the clay mineral montmorillonite as it undergoes wetting and drying [35].…”
Section: Introductionmentioning
confidence: 99%
“…In potassium-containing aluminosilicates it has been shown that from the position of the centre-of-gravity (cg) of the static 39 K resonances, the tectosilicate orthoclase (~205 ppm) could be distinguished from phyllosilicates in which the cg position is below 40 ppm [35]. Potassium NMR could also distinguish structural and exchangeable potassium in the clay mineral montmorillonite as it undergoes wetting and drying [35]. For potassium aluminosilicate geopolymers the cg positions varied from −47 ppm (more typical of a hydrated potassium phase) in the unheated geopolymer, to −120 ppm in the material heated at 1300 o C, consistent with the position of an unheated feldspar [11].…”
Section: Introductionmentioning
confidence: 99%